2013
DOI: 10.5005/jp-journals-10003-1125
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of Infraorbital Foramen in Dry Human Adult Egyptian Skulls, Anthropometric Measurements and Surgical Relevance

Abstract: Objectives: Evidence supports a clear racial variation in the position of the infraorbital foramen (IOF). Therefore detailed knowledge of the population specific data on biometric features of (IOF) will facilitate therapeutic, diagnostic and surgical manipulations in the maxillofacial region. The goal of this study was to elucidate the morphological features and precise anatomical position of the (IOF) with reference to surrounding anatomical landmarks in an adult Egyptian population. Materials and methods:Fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
2
1
1
Order By: Relevance
“…followed by a position in between the first and second upper premolar teeth (34.4% and 26.5% on the right and left side, resp.). This observation supports the findings of previous reports showing that the IOF is commonly related to the vertical plane passing through the tip of the buccal cusp of the maxillary second premolar tooth [5, 23]. However, according to Aziz et al [3], the maxillary tooth most commonly found in the same vertical plane as the IOF was the first premolar.…”
Section: Discussionsupporting
confidence: 91%
“…followed by a position in between the first and second upper premolar teeth (34.4% and 26.5% on the right and left side, resp.). This observation supports the findings of previous reports showing that the IOF is commonly related to the vertical plane passing through the tip of the buccal cusp of the maxillary second premolar tooth [5, 23]. However, according to Aziz et al [3], the maxillary tooth most commonly found in the same vertical plane as the IOF was the first premolar.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of an AIOF and the accessory branch of the infraorbital nerve raises a mark of caution to both the surgeons and anesthetists as an injury to this branch during surgical maneuvering in the maxillofacial region can result in a sensory deficit and when administering the infraorbital nerve block it may result in insufficient anaesthesia in the region. Double and triple IOF, or accessory foramina were not encountered in the present study, although an occurrence as 2.2-18.2 and 0.5-1.28 %, respectively, has been reported in several previous studies (Leo et al;Aziz et al, 2000;Apinhasmit et al;Boopathi et al;Ilayperuma et al;Elsheikh et al;Dagistan et al;Potu et al;Sokhn et al).…”
Section: Discussioncontrasting
confidence: 53%
“…The IOF may have an accessory foramen by its side, which may be single or multiple. The occurrence of multiple/ accessory infraorbital foramina (AIOF) is extensively reported in the literature (Apinhasmit et al, 2006;Boopathi et al;Ilayperuma et al;Elsheikh et al;Dagistan et al;Potu et al;Sokhn et al). As early as in 1875 Gruber reported that the number of accessory IOF may vary from 1 to 5 (Leo et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em nosso estudo, encontramos alguns aspectos morfológicos interessantes como a predominância da forma oval (45%) seguido de circular e semilunar, esses resultados corroboram com estudos com população de crânios indianos (Potu et al, 2019) neste mesmo estudo foi encontrado formato triangular, enquanto em estudos com crânios de população egípcia a predominância é descrita como semilunar em 54% das amostras (Elsheikh et al, 2013b(Elsheikh et al, , 2013a.…”
Section: Discussionunclassified